THE EFFECTIVENESS OF ZAKAT, INFAQ, AND SADAQAH (ZIS) COLLECTION AT BAZNAS HULU SUNGAI TENGAH REGENCY AMONG REGIONAL WORK UNITS (SKPD) - Anna Maryati; Agus Surya Dharma; Nur Mahbubah (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
This study evaluates the performance of the Hulu Sungai Tengah Regency BAZNAS (National Zakat Agency) in collecting ZIS funds within the Regional Work Units (SKPD), which is driven by the phenomenon of minimal zakat realization from civil servants (ASN) and weak regulatory synergy with the local government. Using descriptive qualitative methods through purposive sampling of leaders, staff, and ASN, this study reveals that although the digitalization strategy and the "jemput zakat" program have shown quite good results, these achievements have not yet reached their maximum potential. The main obstacles identified are the lack of comprehensive socialization, the suboptimal role of the UPZ (Zero-Zone Unit), and the absence of a formal legal framework mandating ZIS deductions for government employees. As a strategic solution, the researcher recommends strengthening operational budget management and urging the Regional Government to immediately issue official regulations or circulars to bind ASN commitments. With a strong legal basis and increased spiritual awareness, it is hoped that zakat potential within the government can be mapped and collected more efficiently and accountably.